POLEMIK MASYARAKAT RIAU DAN PEMERINTAH PROVINSI RIAU TERHADAP PERKEMBANGAN KELAPA SAWIT DI PROVINSI RIAU - I Dewa Ayu Putri Wirantari (Majalah Ilmiah Widyacakra, 2018)
The increasing world demand for palm oil (CPO) has caused the government to continue expanding palm oil plantations. Riau is the province with the largest oil palm plantation in Indonesia. The area of ​​oil palm plantations in Indonesia is 13.5 million ha, of which 2.9 million ha are in riau.1 This certainly has an impact for the people in Riau province.One positive impact for the people of Riau with the development of oil palm plantations is the increase in income and the opening of employment. It is undeniable that oil palm is a commodity that is classified as providing a great income, so it is not surprising if the people are competing to do business in the field of oil palm plantations. The negative impact is that the expansion is done by burning and cutting down the forest, whose effect is remarkable. As happened in the year 2014, when massive forest fires committed in Riau province resulted in excessive smoke pollution. The smoke effects are not only felt in Riau area but also other regions and even neighboring countries also feel the impact of this forest burning. From the pollution of the smoke is a lot of losses felt by the community, ranging from the many people who contracted the disease ARI, can not leave the house, school, or work, all access outside the area of ​​land, sea or air covered by the thick smoke that menggagga visibility, all of which lead to disadvantage of the community, such as education sector to economic sector.